"The world's most hostile environment": how the tobacco industry circumvented Singapore's advertising ban. (24th November 2004) - Assunta, M; Chapman, S
Abstract : Objective: To review how tobacco transnational companies conducted their business in the hostile environment of Singapore, attempting to counter some of the government's tobacco control measures; to compare the Malaysian and the Singaporean governments' stance on tobacco control and the direct bearing of this on the way the tobacco companies conduct their business. Methods: Systematic keyword and opportunistic website searches of formerly private internal industry documents. Results: The comprehensive prohibition on advertising did not prevent the companies from advertising cigarettes to Singaporeans. Both British American Tobacco and Philip Morris used Malaysian television to advertise into Singapore. To launch a new brand of cigarettes, Alpine, Philip Morris used a non-tobacco product, the Alpine wine cooler. Other creative strategies such as innovative packaging and display units at retailers were explored to overcome the restrictions. Philip Morris experimented with developing a prototype cigarette using aroma and sweetened tipping paper to target the young and health conscious. The industry sought to weaken the strong pack warnings. The industry distributed anti-smoking posters for youth to retailers but privately salivated over their market potential.